Sukun ‘Sing Penting Duite’; Redifining Custom in New Normal Era - Rahmat Fajar; Eka Wahyuningsih, Mirotin; Assiddiqi, Hasbi Assiddiqi (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
Many television commercials participate in campaigning the awareness of covid-19 virus spread as well as the implementation of New Normal which is defined as the time to follow health protocol while maintaining the distance from others, in adapting with the existence of the virus. The commercial of Sukun, in the episode of “Sukun lebaran 2021 “sing penting duite”, also partakes in informing public on the significance of celebrating Idul Fitri with the smallest and closest group of people in order to be safe from the virus. This portrayal is unlike Indonesia’s decades of customs in celebrating this Islamic Holiday by mudik, gathering with many people, and visiting others’ houses. In order to analyze this advertisement in relaying positive campaign, this research employs qualitative method specifically Gillian Rose’s Visual Methodology. Rose defines meaning of images is completed at three sites; the image itself, the production of the image, and the audience. Meaning of image made by the image itself is selected as approach in gaining more focused analysis. In addition, this research employs Stuart Hall’s representation theory regarding the adjustment in celebrating the day. The research finds that the brief commercial employs simple language so that the message becomes informative and persuasive. Hence, “sing penting duite” is established as the center of attention. The presented visual which compared the past and today celebration highlights the changing and the effort to adapt with current situation. Afterward, this also signifies the support and empowerment toward the viewer during this global pandemic.